RETRACTED : The Influence of Incentives, Work Environment and Work Discipline on Employee Satisfaction of PT Xyz Cakung Branch - Norika Filda Sianturi; Herry Krisnandi; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2024)
This study aims to analyze how much influence incentives, work environment and work discipline have on employee job satisfaction. In this study using primary data obtained from the distribution of questionnaires to 142 employees as respondents at PT, XYZ cakung branch. This study used descriptive analysis methods and inferential analysis. Data were analyzed using multiple linear regression correlation analysis, instrument test, model feasibility test, and t test. The results of this study show a positive and significant influence on employee job satisfaction, resulting from the results of the regression equation model in the Coefficients table Y = 4.307 + 0.246 + 0.241 + 0.202. In the feasibility test of the model, a significant value of 0.000 was obtained, which means that the model is said to be significant and the model is said to be feasible to be used in this study. In the results of the t-test hypothesis value, the sig value on the incentive variable is 0.000, the sig value on the work environment variable is 0.008, and the sig value on work discipline is 0.000. So it can be concluded that partially these three variables have a positive and significant influence on the dependent variable of employee performance. If the management provides good incentives and creates a comfortable and conducive work environment as well as implementing good discipline in the work environment to stimulate employees to do their jobs better, it will be able to influence employees to do their jobs better. Which will have an impact on achieving common goals